2000
DOI: 10.1046/j.1365-2761.2000.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac disorders in farmed adult brown trout, Salmo trutta L.

Abstract: During summer in Brittany, France, sea farmed brown trout, Salmo trutta L., regularly experience a high mortality rate which is associated, at least in part, with cardiac disorders (aneurysms and infarcts). The present study is preliminary to a more extensive research programme, the objective of which is to determine to what extent the physiological performance of the cardiovascular system of brown trout is affected by the environmental conditions the fish experience in farm cages. We conducted a 2-week in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
1
23
0
1
Order By: Relevance
“…It appears, both from our own experience as well as reports from Canada and France (Mercier et al 2000, Brocklebank & Raverty 2002) that abnormally shaped hearts and misaligned vessels might be a widespread problem that has so far been overlooked in fish farming. The reduced cardiovascular capacity might cause severe losses due to increased mortality and reduced growth rate.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It appears, both from our own experience as well as reports from Canada and France (Mercier et al 2000, Brocklebank & Raverty 2002) that abnormally shaped hearts and misaligned vessels might be a widespread problem that has so far been overlooked in fish farming. The reduced cardiovascular capacity might cause severe losses due to increased mortality and reduced growth rate.…”
Section: Discussionmentioning
confidence: 76%
“…These include arteriosclerosis (Farrell 2002), anomalies in heart rate (Mercier et al 2000), aplasia of septum transversum (Poppe et al 1998), situs inversus of the heart (Kaada & Hopp 1995), hypoplasia of the outer, compact ventricular myocardium (Poppe & Taksdal 2000) and cardiac hernia with myocardial hypoplasia (Poppe et al 2002). Common to all these abnormalities is restricted cardiac function, manifested by reduced tolerance to transportation, handling, grading and anaesthesia.…”
Section: Oncorhynchus Mykissmentioning
confidence: 99%
“…When rainbow trout swim, or when they are given an intraarterial adrenaline injection, both Q and diastolic ventral aortic pressure increase, but mean pressure rarely exceeds 8·kPa (Kiceniuk and Jones, 1977;Gamperl et al, 1994). The heart was then returned to the control perfusion conditions for a 15·min recovery and equilibration with a new adrenaline concentration (1·µmol·l -1 ) in the perfusate, which was then used to assess the effect of maximum adrenergic stimulation of the heart (see Mercier et al, 2000). The two adrenaline concentrations used (5·nmol·l -1 and 1·µmol·l -1 ) span the range for circulating catecholamine levels observed in resting and stressed trout, respectively (Milligan et al, 1989;Randall and Perry, 1992;Gamperl et al, 1994).…”
Section: Fish Holding and Screeningmentioning
confidence: 99%
“…A number of studies have reported the development of various heart deformities in salmon farmed under intensive aquaculture conditions, as a result of both hyperplasia and hypertrophy (Poppe and Taksdal 2000;Poppe et al 2002Poppe et al , 2003Gamperl and Farrell 2004;Takle et al 2006). While the most reported cardiac deformity is heart hypertrophy and altered ventricle shape (Poppe et al 2003), other reported deformities in farmed salmon include increased levels of fat deposition (Gamperl and Farrell 2004) arteriosclerosis (Farrell 2002) and anomalies in heart rate (Mercier et al 2000).…”
Section: Introductionmentioning
confidence: 99%